ANALISIS TINGKAT LITERASI SAINS MAHASISWA TERHADAP ISU KIMIA AKTUAL BERBASIS MIKROPLASTIK - Yulika Hotrina Turnip; Ade Rani Nikita; Marisa Manullang; Hotman Priwaldi Sijabat; Syifa Namira Damanik; Hendra Kurnia Pulungan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the level of students’ scientific literacy regarding current chemistry issues based on microplastics. The research employed a quantitative approach with a descriptive method. The subjects consisted of 52 students from several education and science study programs, namely Chemistry Education, Biology Education, Physics Education, and Mathematics Education. The sampling technique used was purposive sampling. The research instrument was a scientific literacy questionnaire based on a Likert scale consisting of 20 statements covering indicators of understanding scientific concepts, explaining phenomena, interpreting scientific data, evaluating scientific information, science-based decision-making, and environmental awareness. The data were analyzed descriptively using percentages. The results showed that the students’ level of scientific literacy regarding microplastic issues was in the high to very high category. The environmental awareness indicator obtained the highest percentage at 92%, while the science-based decision-making indicator obtained the lowest percentage at 82%, although it was still categorized as high. Overall, the findings indicate that students have a good understanding of microplastic issues and are able to relate them to scientific concepts. These findings suggest that microplastic issues can be utilized as a learning context to improve students scientific literacy.